Developmental the pattern of embryogenic microspore of rice (Oryza sativa L.) based on morphological characteristic - Siti Nurbaiti; Yekti Asih Purwestri; Budi Setiadi Daryono; Endang Semiarti; Ari Indrianto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2019)
Microspore culture is a rapid approach to get double haploid plants in shorten time which is important for plant breeding. Microspore culture of pigmented rice cultivar Segreng was used to observe the pattern of embryogenic development based on the characteristics of morphology. Characterization between embryogenic and non-embryogenic microspores was conducted after exposed anther to carbohydrate starvation in B medium culture at 33oC for 4 days. The result showed that enlarged microspore and star-like structure of fragmented cytoplasm become a marker of embryogenic microspore after stresses treatment. More complex of fragmented microspore was found at 4 days in A2 medium and developed further into multicellular structure. These multicellular structures might be originated either by symmetrical or asymmetrical division. The longer incubation, the higher frequency of complex fragmented microspore that developed into multicellular structure release from exine has appeared.